Protective Effects of Polysaccharides in Neurodegenerative Diseases - Wang, Yinying; Chen, Rongsha; Yang, Zhongshan; Wen, Qian; Cao, Xia; Zhao, Ninghui; Yan, Jinyuan (Frontiers in Aging Neuroscience, 2022)
Neurodegenerative diseases (NDs) are characterized by progressive degeneration and necrosis of neurons, including Alzheimer's disease, Parkinson's disease, Huntington's disease and others. There are no existing therapies that correct the progression of these diseases, and current therapies provide merely symptomatic relief. The use of polysaccharides has received significant attention due to extensive biological activities and application prospects. Previous studies suggest that the polysaccharides as a candidate participate in neuronal protection and protect against NDs. In this review, we demonstrate that various polysaccharides mediate NDs, and share several common mechanisms characterized by autophagy, apoptosis, neuroinflammation, oxidative stress, mitochondrial dysfunction in PD and AD. Furthermore, this review reveals potential role of polysaccharides in vitro and in vivo models of NDs, and highlights the contributions of polysaccharides and prospects of their mechanism studies for the treatment of NDs. Finally, we suggest some remaining questions for the field and areas for new development.